Results of a clinical study of the influenza tetravalent inactivated subunit adjuvant vaccine Grippol Quadrivalent in children aged 6 months to 5 years (inclusive) - Viktor V. Romanenko; Leyla S. Namazova-Baranova; Alina A. Kotova; Kamilla E. Efendieva; Anna A. Ruleva; Ekaterina A. Khait; Olga A. Perminova; Tatiana E. Pak; Svetlana G. Lazareva; Liubov V. Aleshina; Dmitriy A. Suprun; Anna N. Galustyan; et al. (Педиатрическая фармакология)
The article presents the results of a clinical investigation on the administration of the Grippol Quadrivalent vaccine (influenza tetravalent inactivated subunit adjuvant vaccine) in children from 6 months to 5 years old. The vaccine has demonstrated no less effectiveness in comparison with the Grippol plus vaccine (influenza trivalent inactivated polymer-subunit vaccine).comparable results were obtained for all evaluated indicators of immunological efficacy against matching strains of the influenza virus, while for additional strain B (Yamagata line) there was a statistically significant difference in the increase in the immune response in the Grippol Quadrivalent group. The results of the assessment of the reactogenicity and frequency of systemic adverse events indicated a favorable and comparable safety profile of the vaccines Grippol Quadrivalent and Grippol plus in children from 6 months to 5 years old. The data obtained allowed us to conclude that the immunological efficacy of the Grippol Quadrivalent vaccine is no less when compared to the Grippol plus vaccine, as well as a comparable safety and reactogenicity profile. According to the results of the clinical investigation, on 08/04/2023, the Ministry of Health of the Russian Federation amended the “Instructions for the medical use of the drug”: Grippol Quadrivalent is indicated for children from the age of 6 months.